Self-destruction in the formation of addictive and neurotic disorders: suicidal and risk-taking behaviour - N. A. Bokhan; I. V. Voevodin (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2018)
This paper considers two forms of self-destructive behaviour in groups of young highly educated patients with dependencies (F1) and neurotic disorders (F4). The prevalence of suicidal ideation was 25.5% and risk-taking behaviour 18.2%. These symptoms are negatively correlated with each other, characterized by different pathopsychological and psychopathological relationships. Suicidality is detected mainly in neurotic disorders and characterized by a reduced adaptation, low frustration tolerance, and maladaptive coping. Risk-taking behaviour is more related to addictive disorders, irrational cognition of self-imposed obligation, and a fairly high level of adaptation. Accordingly, there were proposed differentiated programs of cognitive-behavioural coping prevention of self-destructive behaviour.